Republic of Korea : Financial Sector Assessment Program-Stress Testing And Financial Stability Analysis-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
The financial stability assessment under the Financial Sector Assessment Program (FSAP) for Korea was carried out in close collaboration with the authorities. The assessment included top- down (TD) and bottom-up (BU) stress testing of Korea's commercial banks and certain non-bank depository institutions (NBDIs); and evaluation of the potential contagion across banks (stemming both from funding pressures and potential defaults). The FSAP team did not have access to confidential supervisory data for the stress tests and the contagion analyses.2 The practice of withholding information in the context of an FSAP, while undesirable, is also observed in other FSAPs. As a result, the analyses were carried out by the authorities in cooperation with participating banks, with the FSAP team performing extensive methodological and estimation validations of the results. The stress testing exercise included TD and BU stress tests of banks' solvency and liquidity. For the solvency analysis, the TD tests were based on the internal Systemic Risk Assessment Model for Macroprudential Policy (SAMP) developed by the Bank of Korea (BOK), complemented by macroeconomic projections from the BOK's macroeconomic model. These were supplemented by BU tests, carried out by individual banks. For the liquidity analysis, the TD tests were carried out by the Financial Supervisory Service (FSS), with separate assessments of banks' local currency and foreign exchange (FX) liquidity risks. BU tests of liquidity were performed by individual banks, and were based on a different set of assumptions on potential liquidity outflows. All stress tests were based on assumptions and parameters agreed between the authorities and the FSAP team.